Development of Organic Fertilizer Granulator for Household Users - มงคลชัยชนะ สมบัติย์ (KKU Science Journal, 2013)
The research aims to construct organic fertilizer granulator for household use and also to find its productive efficiency. Satisfaction of users is also included, particularly in the crusher and the separator units. The crusher unit has an average capacity of 40.62 kg/h. Users’ satisfaction is at high level (3.51). The granulator unit has an average capacity of 66.22 kg/h. About 65.97% of fertilizer granules are 3-6 mm. in size; about 9.24% is larger than 6 mm. in size; about 26.30% is smaller than 3-1 mm in size; and about 0.49% is smaller than 1 mm in size. Amount of water used is 72.52 cm2/kg. Users’ satisfaction is at high level (3.72). And the separator unit has an average capacity of the unit is 147.66 kg/h, with 2.47% of residue. Its efficiency in separating fertilizer granules is more than 98% correct. Users’ satisfaction is at high level (3.67).